1993
DOI: 10.1007/bf00233063
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of tryptophan decarboxylase, strictosidine synthase and strictosidine glucosidase in suspension cultured cells of Catharanthus roseus and Tabernaemontana divaricata

Abstract: The subcellular localization of tryptophan decarboxylase, strictosidine synthase and strictosidine glucosidase in suspension cultured cells of Catharanthus roseus (L.) G. Don and Tabernaemontana divaricata (L.) R. Br. ex Roem. et Schult, was investigated. It was found that tryptophan decarboxylase is an extra-vacuolar enzyme, whereas strictosidine synthase is active inside the vacuole. Strong indications were obtained for the localization of strictosidine glucosidase on the outside of the tonoplast. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Substrate specificity studies have suggested that only loganin can serve as a substrate for SLS (Yamamoto et al, 2000). The association of this cytochrome P450 with endoplasmic reticulum membranes or related vesicles could rapidly convert loganin into secologanin followed by its transfer to the vacuole (Contin et al, 1999) together with tryptamine for conversion into strictosidine by vacuole-associated STR (Stevens et al, 1993). In this way, the SLS-mediated conversion of loganin into secologanin, together with its subcellular compartmentalization for MIA biosynthesis, could prevent loganin from inhibiting LAMT.…”
Section: Kinetic Analyses and Substrate Specificity Studies With Rlammentioning
confidence: 99%
“…Substrate specificity studies have suggested that only loganin can serve as a substrate for SLS (Yamamoto et al, 2000). The association of this cytochrome P450 with endoplasmic reticulum membranes or related vesicles could rapidly convert loganin into secologanin followed by its transfer to the vacuole (Contin et al, 1999) together with tryptamine for conversion into strictosidine by vacuole-associated STR (Stevens et al, 1993). In this way, the SLS-mediated conversion of loganin into secologanin, together with its subcellular compartmentalization for MIA biosynthesis, could prevent loganin from inhibiting LAMT.…”
Section: Kinetic Analyses and Substrate Specificity Studies With Rlammentioning
confidence: 99%
“…For example, enzymes of the monoterpenoid indole alkaloid pathway in Catharanthus roseus have been localized to the cytosol (De Luca and Cutler, 1987), vacuole (McKnight et al, 1991), tonoplast (Stevens et al, 1993), thylakoid membranes (De Luca and Cutler, 1987), and endoplasmic reticulum (ER; St-Pierre and De Luca, 1995). The involvement of multiple subcellular compartments is also apparent in the biosynthesis of quinolizidine alkaloids.…”
mentioning
confidence: 99%
“…In particular, we wanted to examine the effects of localizing TDC to the chloroplast, the site of biosynthesis of the enzyme's natural substrate, l-Trp (Radwanski and Last, 1995). We also studied the effects of targeting TDC to the endoplasmic reticulum (ER) because it has been demonstrated that targeting proteins to the ER (Iturriaga et al, 1989;Wandelt et al, 1992; Boevink et al, 1996) significantly enhances accumulation of the respective recombinant protein in plant cells (Fiedler et al, 1997; Gomord et al., 1997;Fischer et al, 1999).TDC is a cytosolic enzyme in TIA-producing plants such as C. roseus (De Luca and Cutler, 1987;Stevens et al, 1993), and ideally, studies on localization of TDC should be carried out using transgenic material from the plant expressing TDC as part of the pathway of interest; in our case, TIA biosynthesis in C. roseus. However, although transgenic undifferentiated C. roseus cell cultures can be recovered with relative ease, TIA biosynthesis is severely impeded in such cultures.…”
mentioning
confidence: 99%
“…TDC is a cytosolic enzyme in TIA-producing plants such as C. roseus (De Luca and Cutler, 1987;Stevens et al, 1993), and ideally, studies on localization of TDC should be carried out using transgenic material from the plant expressing TDC as part of the pathway of interest; in our case, TIA biosynthesis in C. roseus. However, although transgenic undifferentiated C. roseus cell cultures can be recovered with relative ease, TIA biosynthesis is severely impeded in such cultures.…”
mentioning
confidence: 99%